Analysis of the Judgment of the Majority of the Constitutional Court in the Case of the Pontifical Catholic University of Peru and the Inheritance of Mr. Riva Agüero - Rubio Correa, Marcial (2010)
The following paper develops a legal analysis of the verdict issued by the Constitutional Court which declared unfounded the resource of affront constitutional, the writ of Amparo, filed by the Pontifical Catholic University of Peru. The issue under discussion is about who should exercise the disposition of the property of the inheritance of Mr.Riva Agüero. On the one hand, the Administrative Assembly demands this right and on the other hand, the PUCP is protected in its right of university autonomy and property. Hence, the author emphasizes the need of using an appropriate methodology of foundation in the development of the verdict. This development considers the concept of property and constitutional heritage that is different and broader than the civilian concept. The following sections from this paper, explain how the foundations of the majority of the Constitutional Court, published on April 19, 2010, do not correspond to a proper argumentation according to the precedent jurisprudence in constitutional matters with respect to the legal categories mentioned. Therefore, the validity of six foundations will be analyzed using the national legislation as well as national jurisprudence. The first of them refers to the different testaments issued between 1933 and 1938; and which of them should predominate. The second, third and fourth arguments develop if the Constitutional Court has the competence to determine whether a legal act is invalid or not. Added to this, if the TC can resolve on the issue of representation before the Assembly of Directors, and finally if it is the TC who can determine the validity of a legal act. In the fifth argument, it is showed an analysis of the testament regarding the participation of the Archbishop of Lima. Based on previous information, the author determines the arguments which are deficient and invalid. As a consequence, all this contributes to a discriminatory methodology towards the PUCP carried out by the Constitutional Court.